Identification of causal education effects using a discontinuity in school entry tests: First results from a pilot study - Stefan Boes; Dominik Hangartner; Lukas Schmid (University of Bern, Department of Economics, 2011)
We use a credible regression discontinuity design to estimate causal education effects. Pupils in the Swiss education system had to pass a centrally organized exam that classified them into different levels of secondary school, and that ultimately determined their educational degree. A major feature of this exam was the local randomization around the classification threshold due to the impossibility of strategic sorting. Our preliminary results suggest large and significant effects on earnings, political interest, and attitudes toward immigrants. The extension to a wider set of data is part of ongoing research.
Keywords: D72; I21; J15; J31; 330; returns to education; causality; endogeneity; regression discontinuity; Bildungsertrag; Bildungsniveau; Schüler; Test; Schulauswahl; Schweiz